Seeking Optimal Management for Radioactive Iodine Therapy-induced Adverse Effects - Charalambous, Andreas (My University, 2017)
Radioactive iodine therapy (RAIT) is one of the important treatment modalities in the management of differentiated thyroid cancer (DTC). RAIT with iodine-131 has long been used in the management of DTC for the ablation of residual thyroid or treatment of its metastases. Despite being reasonably safe, radioiodine therapy is not always without side effects. Even relatively low administered activities of RAIT used for remnant ablation have been associated with the more clinically significant side effects of sialadenitis, xerostomia, salivary gland pain and swelling, dry eyes, excessive tearing, or alterations in taste in as many as 25% of patients. Given that there is a lack of comprehensive management of these RAIT-induced adverse effects, this paper explores the use of other nonpharmacological measures and their effectiveness as interventions to minimize salivary gland damage.
Keywords: Nonpharmacological; Salivary gland side effects; Radioiodine